PENGARUH AKTIVITAS PEMASARAN MEDIA SOSIAL DAN SELEBRITI ENDORSER TERHADAP KESADARAN MEREK HOTEL X BALI - I Made Gemaharta Dwi Cita; I Nyoman Sudiksa; Ida Ayu Kalpikawati; Ni Wayan Chintia Pinaria (Fakultas Ekonomi Universitas Warmadewa, 2023)
The purpose of this study was to analyze (1) the impact of social media marketing activities on brand awareness, (2) the impact of celebrity endorser on brand awareness, and (3) the impact of social media marketing activities and celebrity endorser simultaneously on brand awareness Hotel X Bali. Questionnaires as the data collection technique were distributed to 100 followers of Hotel X Bali’s Instagram. The data analysis technique consisted of classical assumption test, multiple linear regression analysis, t-test, F-test, coefficient of determination, and effective contribution by using SPSS for windows version 26 program. The results of this study indicated that (1) social media marketing activities had a positive and significant effect on brand awareness, (2) celebrity endorser had a positive and significant effect on brand awareness, and (3) social media marketing activities and celebrity endorser simultaneously had a positive and significant effect on brand awareness at Hotel X Bali. Social media marketing activities and celebrity endorser influenced 54% on brand awareness, while the remaining 46% was caused by other variables that were not investigated in this study. Based on the results of this study, Hotel X Bali should publish trendy content on Instagram, collaborate with celebrity endorsers that are relevant to Hotel X Bali’s target market, choose celebrity endorsers who have a good image in the community, and Hotel X Bali should maximize the use of digital marketing such as Search Engine Optimization, Email Marketing, and One Public Relations to increase brand awareness.